Food safety culture in onsite foodservices: development and validation of a measurement scale - Ungku Zainal Abidin, Ungku Fatimah; Arendt, Susan W.; Strohbehn, Catherine H. (Foodservice Systems Management Education Council and The National Association of College & University Food Services, 2014)
The purpose of this research was to develop and validate a measurement scale for food safety culture in onsite foodservices. Nonsupervisory employees in hospital and school foodservices participated in a two‐phase, mixed methods research design process. In phase 1, four focus groups were conducted to identify relevant factors of food safety culture. In phase 2, a survey completed by 582 respondents appeared to validate six food safety culture factors: management and coworkers support, communication, self‐ commitment, environment support, work pressure, and risk judgment. The scale can be used to assess current food safety practices and strategize future food safety improvement goals.